Post-surgical efficacy of early motion on intra-articular distal radius fracture and the effect of osteoporosis on outcomes (Annals of Medical Research, 2024)
Aim: Post-surgical rehabilitation of intra-articular distal radius fractures in osteoporotic patients is still controversial. The aim of our study is to compare the effectiveness of early and late motion in intra-articular distal radius fractures in osteoporotic and non-osteoporotic patients.Materials and Methods: Eighty patients were included in our study. The patients were divided into two groups according to osteoporosis (OP), (OP +, OP -). Each group was also divided into 2 groups according to initiation of motion ((Early motion subgroup (E-MOT), Late motion subgroup (L-MOT)). Quick Disabilities of the Arm, Shoulder and Hand (Q-DASH), Patient-Rated Wrist Evaluation (PRWE) scores, Range of Motion (ROM) and grip strength were evaluated at final follow-up.Results: No significant difference was found among the groups in terms of age, gender ratio, right hand–left hand ratio, hand dominance, follow-up duration, or fracture classification. Contrary, the range of motion and functional results of OP+,E-MOT group were found to be more successful than the OP+,L-MOT group, there was no significant difference between the OP-,EMOT group and the OP-,L-MOT group.Conclusion: Early motion has a positive effect on the results in osteoporotic patients compared to late motion, while it does not significantly affect outcomes in non-osteoporotic patients. Early motion after surgery for intra-articular distal radius fractures is crucial for osteoporotic patients, but less so for non-osteoporotic patients.